An identity threat perspective on why and when employee voice brings abusive supervision - Wu, Lei; Long, Anna; Hu, Chenbang; Xu, Yunpeng (Frontiers in Psychology, 2023)
Purpose Drawing from identity threat theory, this study aims to understand how and when employee voice can lead to abusive supervision. It proposes and examines a theoretical model in which employee voice is linked to abusive supervision through the mediating effect of leader identity threat. Methods We conducted a field study by collecting data from 93 supervisors and 533 subordinates in China at two different points in time. A structural equation model and Mplus software were used to examine the direct relationship between employee voice and abusive supervision, as well as the mediating effect of leader identity threat and the moderating effect of supervisor traditionality. Results Our results showed that employee voice was positively related to leader identity threat and had an indirect effect on abusive supervision via leader identity threat. In addition, we found that supervisor traditionality moderated the relationship between employee voice and leader identity threat. Subordinates’ voice increased perceptions of leader identity threat among supervisors with high traditionality, whereas supervisors with low traditionality did not make this association. Finally, the indirect effect of employee voice on abusive supervision via leader identity threat was moderated by supervisor traditionality. Discussion First, this study broadens our understanding of the antecedents of abusive supervision by proposing that employee voice may induce abusive supervision. Second, it develops an identity threat perspective to explain why employee voice is positively related to abusive supervision. Finally, it enriches the research on implicit leadership theories by proposing that supervisors’ cultural values can also influence supervisors’ sense-making of subordinates’ behaviors.